Effectiveness and Quality of Education: Methodology, Organization and Technical Means - Juška, V.; Chaziachmetovas, A.; Jaruševičius, R. (Elektronika ir Elektrotechnika, 2010)
The paper presents an active learning method, which is applied in electronics and basic circuit theory. An essential feature of this methodology - theory, simulation and hands-on laboratory combined in a fully computerized workplace. The objective of training methodology provides the student with more freedom to increase personal responsibility and motivation.